2021
DOI: 10.1002/iub.2539
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous dipeptide‐carnosine supplementation ameliorates hypobaric hypoxia‐induced skeletal muscle loss via attenuating endoplasmic reticulum stress response and maintaining proteostasis

Abstract: High altitude is an environmental stress that is accompanied with numerous adverse biological responses, including skeletal muscle weakness and muscle protein loss. Skeletal muscle wasting is an important clinical problem, progressing to critical illness, associated with increased morbidity and mortality. The present study explores the protective efficacy of endogenous dipeptide, carnosine (CAR), supplementation in ameliorating skeletal muscle protein loss under hypobaric hypoxia (HH). Male Sprague–Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In recent years, nutritional strategies have emerged and it has been well demonstrated that they can increase the level of production and improve the health of animals and products obtained from them [16], as well as to enhance livestock productivity [17,18]. There is evidence that L-carnosine supplementation ameliorates skeletal muscle protein loss mainly by maintaining proteostasis redox homeostasis in skeletal muscles [19]. In addition, L-carnosine may be beneficial in maintaining higher metabolic activity of muscle fibers [20], both under in vivo [21,22] and in vitro conditions [23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nutritional strategies have emerged and it has been well demonstrated that they can increase the level of production and improve the health of animals and products obtained from them [16], as well as to enhance livestock productivity [17,18]. There is evidence that L-carnosine supplementation ameliorates skeletal muscle protein loss mainly by maintaining proteostasis redox homeostasis in skeletal muscles [19]. In addition, L-carnosine may be beneficial in maintaining higher metabolic activity of muscle fibers [20], both under in vivo [21,22] and in vitro conditions [23].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of hypoxia on muscle mass and function is less investigated compared to inactivity. Several studies have reported that prolonged exposure to hypoxia (in response to various pathological and physiological conditions including high altitude) results in loss of muscle mass, structure, and performance [ 4 , 5 , 6 , 7 ]. Moreover, hypoxia aggravates inactivity-related muscle wasting [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carnosine (Carn) is a histidine dipeptide that is naturally occurring and endogenously generated in human body, carnosine is broadly distributed in the kidney, brain, muscle, stomach and in significant proportions, skeletal muscle [ 28 ]. Numerous biological actions of this dipeptide have been demonstrated, including the capacity to chelate metal ions, anti-oxidant activity, suppressing protein glycosylation, anti-inflammatory impact and anti-senescence properties.…”
mentioning
confidence: 99%